Social institutions and gender inequality in fragile states: Are they relevant for the post-MDG debate? - Boris Sergio Branisa Caballero; Carolina Cardona (Institute for Advanced Development Studies (INESAD), 2015)
We focus on an issue that appears particularly relevant for fragile states and which has received little attention: social institutions related to gender inequality, defined as societal practices and legal norms that frame gender roles and the distribution of power between men and women in the family, market, and social and political life. We show empirically that fragile states perform worse than other non-fragile developing countries when considering these social institutions. We suggest that a special set of indicators reflecting social institutions related to gender inequality in both fragile states and non-fragile states should be considered in the post-MDG agenda.
Keywords: D63; I39; J16; O1; 330; Social institutions; Gender inequality; Developing countries; Fragile States; Millennium Development Goals; Post 2015 Development Agenda